2016
DOI: 10.1177/2326409816679429
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by Which Metabolic Reprogramming in GSD1 Liver Generates a Favorable Tumorigenic Environment

Abstract: Glycogen storage disease type 1 (GSD1) is an inherited disorder caused by impaired glucose 6-phosphatase activity. This impairment translates into the inhibition of endogenous glucose production and the subsequent accumulation of cellular glucose 6-phosphate. Excess glucose 6-phosphate enhances glycolysis, increases the production of fatty acids, uric acid, and lactate, causes hepatomegaly due to glycogen and lipid accumulation, and finally results in liver tumor development. Although the exact mechanisms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 104 publications
(147 reference statements)
0
16
0
Order By: Relevance
“…AST and ALT activity, compared to untreated L.G6pc −/− mice ( Figure 6 D). Furthermore, previous studies showed that the metabolic reprogramming occurring in GSDIa livers, as a consequence of the excessive G6P levels, promotes hepatic tumorigenesis [16] , [25] . Recent data have shown a decrease in tumor suppressors in L.G6pc −/− livers (unpublished data), in accordance with the pre-neoplastic status of G6pc −/− hepatocytes [16] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…AST and ALT activity, compared to untreated L.G6pc −/− mice ( Figure 6 D). Furthermore, previous studies showed that the metabolic reprogramming occurring in GSDIa livers, as a consequence of the excessive G6P levels, promotes hepatic tumorigenesis [16] , [25] . Recent data have shown a decrease in tumor suppressors in L.G6pc −/− livers (unpublished data), in accordance with the pre-neoplastic status of G6pc −/− hepatocytes [16] .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, previous studies showed that the metabolic reprogramming occurring in GSDIa livers, as a consequence of the excessive G6P levels, promotes hepatic tumorigenesis [16] , [25] . Recent data have shown a decrease in tumor suppressors in L.G6pc −/− livers (unpublished data), in accordance with the pre-neoplastic status of G6pc −/− hepatocytes [16] . Interestingly, tumor suppressors, such as AMP-activated protein kinase (AMPK) and phosphatase and tensin homolog (PTEN), were down-regulated in L.G6pc −/− livers, while fenofibrate restored their expression to the level observed in WT mice ( Figure 6 E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All these disturbances contribute to hypertriglyceridemia and hypercholesteridemia observed in diabetes and GSDI. In conclusion, the liver metabolism of diabetes and GSDI is very similar, albeit exacerbated in GSDI, with G6P being at the metabolic crossroad as a main responsible for metabolic reprogramming [39,62].…”
Section: Imbalance Of Glucose-6 Phosphate Metabolism Leads To Metabolmentioning
confidence: 86%